Heart Rate Variability and Cardiovascular Reflex Tests for Assessment of Autonomic Functions in Preeclampsia - Meenakshi Chaswal; Raj Kapoor; Achla Batra; Savita Verma; Bhupendra S. Yadav (International Journal of Hypertension)
Alterations in the autonomic cardiovascular control have been implicated to play an important etiologic role in preeclampsia. The present study was designed to evaluate autonomic functions in preeclamptic pregnant women and compare the values with normotensive pregnant and healthy nonpregnant controls. Assessment of autonomic functions was done by cardiovascular reflex tests and by analysis of heart rate variability (HRV). Cardiovascular reflex tests included deep breathing test (DBT) and lying to standing test (LST). HRV was analyzed in both time and frequency domain for quantifying the tone of autonomic nervous system to the heart. The time domain measures included standard deviation of normal R-R intervals (SDNN) and square root of mean squared differences of successive R-R intervals (RMSSD). In the frequency domain we measured total power (TP), high frequency (HF) power, low frequency (LF) power, and LF/HF ratio. Cardiovascular reflex tests showed a significant parasympathetic deficit in preeclamptic women. Among parameters of HRV, preeclamptic group had lower values of SDNN, RMSSD, TP, HF, and LF (ms2) and higher value of LF in normalised units along with high LF/HF ratio compared to normotensive pregnant and nonpregnant controls. Furthermore, normotensive pregnant women had lower values of SDNN, TP, and LF component in both absolute power and normalised units compared to nonpregnant females. The results confirm that normal pregnancy is associated with autonomic disturbances which get exaggerated in the state of preeclampsia.